#TITLE_ALTERNATIVE# - TJENDANA (NIM 10103021), GITA
Asian option has an interesting characteristic because the price of asian option depends on the price of some stocks before its maturity time. In this final project the main object is arithmetic discrete asian option. The price of this option depends on the sum of the price of some stocks before its maturity time. Pricing this option analytically is not an easy job because we have to determine the probability distribution function of the sum of these stocks. That’s why in many cases we determine the price of asian option numerically and Monte Carlo simulation is one way to make it done. Monte Carlo simulation provides us informations about the price of asian option and its confidence interval. In this final project I use a new method using comonotonic theory from insurance. The result is the confidence interval of the price of asian option and it will be compared with Monte Carlo simulation confidence interval.